2010
DOI: 10.1017/s0317167100010568
|View full text |Cite
|
Sign up to set email alerts
|

Giant Skull and Brain Metastasis from a Neglected Thyroid Papillary Carcinoma

Abstract: This 50-year-old woman presented with headaches, torticollis and a large craniocervical mass which had grown rapidly over the previous four months. She had also a thyroid tumefaction neglected for more than 20 years. Physical examination showed normal vital signs, without neurological deficits. It was an evident bilateral exophtalmia with anterior cervical painful mass originating from both lobes of the thyroid gland. The scalp mass (24 × 12 × 20 cm) was noted on the right temporoparietooccipital region with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…After a thorough search of the English literature, only few other cases of a neglected papillary thyroid carcinoma with the enormous dimensions observed in this case have been reported to the best of our knowledge [12, 13]. There are also two articles regarding distant metastases from a neglected thyroid papillary carcinoma [14, 15]. …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…After a thorough search of the English literature, only few other cases of a neglected papillary thyroid carcinoma with the enormous dimensions observed in this case have been reported to the best of our knowledge [12, 13]. There are also two articles regarding distant metastases from a neglected thyroid papillary carcinoma [14, 15]. …”
Section: Discussionmentioning
confidence: 96%
“…Mostarchid et al reported a case of giant skull and brain metastasis from a neglected thyroid papillary carcinoma [14], while Pavlidis et al investigated the occurrence of subcutaneous scalp metastases [15]. …”
Section: Discussionmentioning
confidence: 99%